Aplicaç\~ao da análise por opç\~oes reais para o abandono contratual em concess\~oes rodoviárias: Proposiç\~ao de remédio regulatório sobre o valor da indenizaç\~ao por investimentos n\~ao amortizados - Felipe Amaral Costa; Fabiano Mezadre Pompermayer (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– When discussing the early termination of concession agreements, compensation for investments in reversible assets is a core issue that directly affects the parties' interests. Without fair economically compensation, in addition to representing a possible act of illicit enrichment on the public administration and an obstacle to the project's bankability, the private partner is subjugated to the actions of the granting authority and, as a result, discouraged to comply with the assumed obligations. On the other hand, excessive values also jeopardize the best performance of the concessionaire in meeting the investments, deadlines, and agreed service levels. To stimulate the debate regarding fair compensation, this Text for Discussion proposes a methodology to calculate indemnity for road concessions early termination. The model suggests limiting the compensation by applying impairment tests based on simulated traffic levels. Using the Real Options Theory, the work assesses the value added by the flexibility of early termination. The results show that the presented method produces better results when it comes to contractual execution since it reduces the incentives given to the concessionaire and to the granting authority to terminate the contract, compared to the current model adopted by Brazilian legislation.
Keywords: H43; H54; 330; compensation for investments in reversible assets; early contractual termination; real options; roadway concessions